HUBUNGAN DAYA LEDAK OTOT LENGAN TERHADAP KEMAMPUAN CEST PASS TIM BASKET SMAN 1 KUBU KECEMATAN KUBU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this research is not maximal capability of being owned by a chest pass baskset team SMAN 1 Kubu. From several opportunities to chest pass, many of which are not effective or convenient in steals opponents. This problem is evident from observations of researchers at the time of the trial and the game, it is suspected because of the explosive power arm muscles owned by the player. Therefore, the purpose of this study was to determine whether there is a corelation explosive power arm muscles to chest pass ability of team basketball SMAN 1 Kubu. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is explosive power arm muscles, while the dependent variable (Y) is the ability of chest pass. This research data obtained from the tests using two hand medicine ball put test and chest pass ability tests. The sample in this study is SMAN 1 Kubu basketball team of 20 people (total sampling). Based on the research results can be concluded as follows: there is a corealtion between the explosive power of the arm muscles to the Chesst Pass ability is accepted, is characterized by the results obtained by the rhitung = 0,526> rtabel = 0.44, followed by t = 2.624> table = 1,734.Keywords : Explosive Power, Arm Muscles, Chest Pass, Basketball